Pelaksanaan dan Alasan Penolakan Putusan Arbitrase Internasional Dalam Sengketa Bisnis (Studi Kasus: Astro All Asia Networks Plc. Vs. Lippo Group) - Nayla Nur Salsabila; Hudi Yusuf (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
International arbitration is one of the preferred mechanisms for resolving cross-border commercial disputes due to its procedural flexibility, the confidentiality it offers to the parties, and the final and binding nature of its awards. This study aims to analyze the legal framework governing the enforcement and refusal of international arbitral awards, as well as its application in the dispute between Astro All Asia Networks Plc. and the Lippo Group. This research employs a normative legal approach by examining statutory regulations, international conventions, and relevant judicial decisions. The findings indicate that the recognition and enforcement of international arbitral awards in Indonesia are governed by the 1958 New York Convention and Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. However, in practice, differences in judicial interpretation remain regarding the authority of national courts over international arbitral awards. The dispute between Astro All Asia Networks Plc. and the Lippo Group demonstrates that the scope of national courts' authority to recognize or refuse the enforcement of international arbitral awards constitutes a significant legal issue, particularly in maintaining a balance between the principle of final and binding awards, national legal sovereignty, and legal certainty for business actors.